Characterization of indigenous ducks in different agroclimatic region of West Bengal - Subhamoy Pal,; Aruna Pal,; JK Chatterjee,; PN Chatterjee, (Journal of Livestock Biodiversity, 2025)
Ducks form one of the most important poultry species next to chicken. In the present study, we have characterized the indigenous ducks of West Bengal phenotypically through quantitative and qualitative traits in three different agroclimatic region of West Bengal, comprising of four districts. Body colour ranges from white to deep brown, either intact or patchy. Males were observed to have better morphometry compared to that of female in all agro-climatic regions. Ducks from Purba Bardhaman district were reported to have better neck length, girth of breast and body length, whereas Ducks from Malda were reported to have less neck length and body length. Characterization of these duck population reveals high homogeneity and important for breed description.